THE EFFECT OF ENTREPRENEURIAL KNOWLEDGE AND ENTREPRENEURIAL SKILLS ON PERFORMANCE WITH MANAGEMENT SKILLS AS MEDIATING VARIABLE IN CULINARY SMES IN KLATEN, CENTRAL JAVA. - Pusparini, Karina Dwi; Judika , Mahendra (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2023)
The purpose of conducting this research is to further analyze (1) the influence of entrepreneurial knowledge on performance, (2) the influence of management skills on performance, (3) the influence of entrepreneurial knowledge on management skills, (4) the influence of entrepreneurial skills on management skills, and (5) the influence of entrepreneurial knowledge and entrepreneurial skills on performance through management skills as a mediating variable. This study is a survey research using an explanatory research type. The required data consist of primary data obtained using a Likert scale questionnaire given to respondents using SPSS 20 software. The results of the research indicate that there is a significant influence of entrepreneurial knowledge on SMEs performance, there is a significant influence of entrepreneurial skills on SMEs performance, and there is a significant influence of entrepreneurial knowledge and entrepreneurial skills on SMEs performance through management skills as a mediating variable.